Fraud Risk Assessment: Effects of Bias, Skepticism, and Complexity with Whistleblowing Climate as Moderator - Gusti Muhammad Rizal; Dewi Diah Fakhriyyah; Afifudin (Universitas Muhammadiyah Malang, 2026)
Purpose: This study aims to examine the effects of unconscious bias, professional skepticism, and audit complexity on fraud risk assessment quality, and to evaluate the moderating role of whistleblowing climate within organizational audit settings. Methodology/approach: A quantitative approach using Partial Least Squares–Structural Equation Modeling (PLS-SEM) was applied to data collected from 70 internal auditors working in manufacturing firms in Gresik, Indonesia. The analysis included assessment of the measurement model and hypothesis testing for both direct and moderating effects. Findings: Results show that professional skepticism significantly improves the quality of fraud risk assessment. Conversely, unconscious bias and audit complexity have negative but statistically insignificant effects. Whistleblowing climate significantly moderates and enhances the influence of professional skepticism but does not moderate the effects of unconscious bias or audit complexity. Practical implications: Organizations should reinforce professional skepticism through structured training and strengthen ethical infrastructures, particularly whistleblowing systems, to support auditor judgment in fraud detection. Originality/value: This study integrates behavioral auditor factors with ethical organizational context, offering new empirical evidence on how whistleblowing climate interacts with auditor characteristics in shaping fraud risk assessment quality.